Commonwealth Caribbean business law - Ramlogan, Rajendra; Persadie, Natalie Renée (Commonwealth Caribbean law series, 2016)
"Commonwealth Caribbean Business Law breaks away from the traditional English approach of treating business law primarily as the law of contract and agency. The book takes a panoramic view of the foundation of various legal systems with a subsequent examination of different areas of legal liability that may affect business activities. These areas include contract law, agency, tort law, criminal law and internet law as significant challenges confronting the business sector. The book primarily targets the development of business law principles in several Caribbean Commonwealth jurisdictions but also, where appropriate, embraces the jurisprudence of other Commonwealth nations such as the United Kingdom, Canada and Australia. With respect to internet law, the proliferation of judicial pronouncements emerging from the United States and their relevance to the Anglophone Caribbean provided the platform for the only non-Commonwealth treatment of a topic. The approach of the book is to use excerpts from judgments so as to allow students, particularly the non-legal student, to understand legal principles as espoused by the judiciary without the filtering bias of the authors"--